FROM VIEWS TO CHECKOUTS: LINGUISTIC LANDSCAPE AND AIDA MODEL ANALYSIS OF INSTAGRAM AND TIKTOK ADVERTISEMENTS - Zuliati Rohmah; F. A. Dhea La Roiba (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
The rising dominance of short-form video platforms like Instagram and TikTok in the digital marketing ecosystem has transformed how commercial messages are crafted, consumed, and acted upon. These social media platforms no longer function solely as communication spaces but also as visually-dynamic marketplaces where textual and multimodal elements play crucial roles in influencing consumer behavior. Within this context, examining the linguistic landscape (hereinafter, LL) of advertisements and their alignment with persuasive marketing principles becomes crucial to understanding how digital advertising drives user engagement and purchasing behavior. This study aims to investigate how Attention, Interest, Desire, Action (henceforth AIDA) marketing principles are represented in the LLs of TikTok and Instagram ads. Specifically, this research examines the integration of visual-textual elements and persuasive techniques in selected advertisements through the combined lens of LL analysis and the AIDA model. Using a qualitative-descriptive approach, this study analyzed fifty advertisements (25 from Instagram and 25 from TikTok) selected using the purposive sampling method based on four criteria. The analytical framework comprised two components: (1) an LL analysis to categorize language choice, typography, and multimodal integration elements, and (2) an AIDA-based coding scheme to evaluate how each ad captures attention, sustains interest, evokes desire, and prompts consumer action. Data were manually coded and thematically interpreted. The findings reveal that advertising on both Instagram and TikTok exhibits a linguistically rich landscape, with bilingual content (Indonesian–English) being most prevalent, and a smaller yet significant presence of multilingual advertisements (Indonesian–English–Thai), especially on TikTok. Moreover, AIDA principles were consistently observable in both platforms, effectively covering the stages from attention to action. However, Instagram advertisements are generally more straightforward and geared toward long-term engagement, while TikTok ads adopt a more narrative-driven approach with a focus on short-term impact. TikTok ads tended to be more emotionally-evocative and action-oriented, while Instagram ads emphasized polished branding and aesthetic appeal. By combining LL analysis and AIDA principles, this study bridges linguistic and marketing perspectives on digital advertisements. The findings contribute to understanding how digital consumer spaces function as hybrid LLs and offer insights for content creators, marketers, and scholars seeking to design impactful, culturally resonant advertisements on short-form video platforms. The study emphasizes the need for advertisers to align linguistic strategies with persuasive structures to maximize reach and conversion in the competitive realm of social commerce.